Las Transferencias Públicas y su impacto distributivo: La Experiencia de los Países del Cono Sur en la década de 2000 - Javier Alejo; Marcelo Bérgolo; Fedora Carbajal (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2013)
– In Latin America the inequality of income has declined in the 2000s. This study applies a variant of the noparametric decomposition methodology proposed by Barros et al. (2006, 2007) to assess the relevance of the households' sources of income, focusing on the importance of public transfers, on changes in inequality of the Southern Cone countries in the 2000s: Argentina, Brazil, Chile and Uruguay. The results suggest that the non-labor income of the households had a significant contribution to the inequality changes in the 2000s in those countries, which was mainly explained by the equalizing effect of the public source of income. The changes in that source and their impact on inequality were closely associated with the implementation or expansion of non-contributive cash transfer programs during the last decade.
Keywords: C15; D31; I38; 330; Einkommensverteilung; Öffentliche Sozialleistungen; Cono Sur